Die kabbalistische Lehrtafel der Antonia von Württemberg: Studien und Dokumente zur protestantischen Rezeption jüdischer Mystik in einem frühneuzeitlichen Gelehrtenkreis - Gruhl, Reinhard (Frühe Neuzeit, 2016)
"Constructed in Bad Teinach, in Germany's Schwarzwald, Antonia von Württemberg's (1613-1679) 'teaching painting' is an original and compelling synthesis of Jewish Kabbala, Christian mystagogy, and Lutheran theology. This collection of studies and documents draws upon extant documentation on the creation of this artwork, mostly in manuscript form, along with contemporary literary descriptions, situating them in their cultural context"--Provided by publisher